A review of the application of discrete event simulation in manufacturing. Issue 2 (March 2021) - Qiao, Dongping; Wang, Yajing
Abstract: Simulation is an important technical means to verify the efficiency of discrete event systems. This paper summarizes the research system of plant simulation software based on discrete event system, including production layout, routing, material distribution, production line and other aspects. Finally, in view of the shortcomings of plant simulation in simulation, the future improvement and research direction are pointed out.